PENERAPAN KLAUSULA BAKU PADA PRASYARAT JUAL BELI JUNK FOOD DITINJAU DARI HUKUM BISNIS - Fiona Vivian; Winda Fitri (UNES Law Review, 2022)
The phenomenon of junk food is growing rapidly at this time. Although most junk food ultimately harms the health of consumers, buying and selling junk food is not illegal. As a general rule, both the seller and the buyer are free to determine the type, content and form of the contract. However, the existence of standard clauses as a means to facilitate sales transactions between producers and consumers has proven to be widely misused by sellers with standard clauses that are detrimental to consumers, such as "for take away food, an additional fee in the form of a takeaway charge is imposed." The application of the standard clause makes the seller has a stronger position and cause losses for the buyer. This type of research is normative legal research. The results show that basically the standard clause is not prohibited, as long as there are no elements that harm other parties. Provisions for the inclusion of standard clauses are regulated in Article 18 of the UU PERLINDUNGAN KONSUMEN. The advantage of using standard clauses in junk food agreements is that it gives consumers the benefits of time efficiency and equal service, but the disadvantage is that consumers do not have the opportunity to negotiate and decide on the contents of the contract, leaving only the choice of accept or leave. As a result, consumers become vulnerable, there is an imbalance of rights and obligations between economic actors and consumers, and consumers are more disadvantaged.